Beyond buzzwords: fostering interdisciplinary and collaborative global health research in Germany and beyond - Cook-Deegan, Maeve; Böge, Kerem; Bruchhausen, Walter; Chagunda, Mizeck; Chaturvedi, Medha; Esen, Meral; Hanefeld, Johanna; Kampmann, Beate; Köhler, Carsten; Köhler, Charlotte; Osei, Francis; Prazeres da Costa, Clarissa; et al. (Global health action, 2024)
Germany has increased its political and financial commitment for global health, but this needs to be backed by a robust global health research ecosystem with strong partnerships in low- and middle-income countries (LMICs). This article suggests pathways for empowering researchers to operate beyond their disciplinary silos and strengthen partnerships across sectors and countries. The authors identify barriers and enablers of operations from a nascent research network in Germany, trusting that this experience can inform other initiatives seeking to stoke interdisciplinary and collaborative global health research. This article represents the culmination of extensive reflections spanning the initial four years of the German Alliance for Global Health Research (GLOHRA). The insights have additionally been informed by an analysis of publicly available reports, internal procedural records, and externally conducted studies based on interviews with researchers and policymakers. GLOHRA has developed a toolbox of practices that foster interdisciplinary research and support capacity-building. Insights indicate that highly interdisciplinary and diverse governance structures and seed-funding for interdisciplinary and cross-sector research with appropriate review processes represent a critical step for achieving these aims. Additionally, inclusive training sessions and networking events help to bridge disciplinary boundaries, equipping researchers to envision the broader context of their work. Despite achievements, challenges persist. Wider support, especially from universities and research institutions, is necessary to make global health research an attractive career path and to reduce bureaucratic barriers for collaborators in LMICs. Sustained, longer-term federal funding mechanisms will also be essential for ongoing progress. Main findings: Germany’s increased commitment to global health includes federal support for initiatives such as the nascent German Alliance for Global Health Research, a 1000+ member network which aims to foster interdisciplinary and collaborative global health research.Added knowledge: This article reveals the structures, funding mechanisms, and capacity-building initiatives that have bolstered progress on network aims.Global health impact for policy and action: Challenges persist and there is a need for sustained federal funding and wider institutional support for global health careers as well as improved conditions to support more equitable research endeavors with partners in low- and middle-income countries. Main findings: Germany’s increased commitment to global health includes federal support for initiatives such as the nascent German Alliance for Global Health Research, a 1000+ member network which aims to foster interdisciplinary and collaborative global health research. Added knowledge: This article reveals the structures, funding mechanisms, and capacity-building initiatives that have bolstered progress on network aims. Global health impact for policy and action: Challenges persist and there is a need for sustained federal funding and wider institutional support for global health careers as well as improved conditions to support more equitable research endeavors with partners in low- and middle-income countries.